Paranasal Sinus Neuroendocrine Carcinoma: A Case Report and Review of the Literature - Nagesh T. Sirsath; K. Govind Babu; Umesh Das; C. S. Premlatha (Case Reports in Oncological Medicine)
Neuroendocrine neoplasms are defined as epithelial neoplasms with predominant neuroendocrine differentiation. They can arise in almost every organ of the body although they are most commonly found in the gastrointestinal tract and respiratory system. Nasal cavity and paranasal sinuses are a rare site for neuroendocrine carcinoma. In contrast to the other regions, neuroendocrine tumours of the sinuses have been reported to be recurrent and locally destructive. Very few cases of paranasal sinus neuroendocrine carcinoma have been reported till date. Difficulty in pathologic diagnosis and rarity of this malignancy have hindered the progress in understanding the clinical course and improving outcomes. We herein report a case of poorly differentiated neuroendocrine tumour of ethmoid and sphenoid sinus with invasion of orbit and intracranial extension. The patient had complete response at the end of chemoradiation and he was disease-free for 9 months duration after which he developed bone metastasis without regional recurrence.